2013
DOI: 10.1371/journal.pone.0073490
|View full text |Cite
|
Sign up to set email alerts
|

CYP2J2 Overexpression Protects against Arrhythmia Susceptibility in Cardiac Hypertrophy

Abstract: Maladaptive cardiac hypertrophy predisposes one to arrhythmia and sudden death. Cytochrome P450 (CYP)-derived epoxyeicosatrienoic acids (EETs) promote anti-inflammatory and antiapoptotic mechanisms, and are involved in the regulation of cardiac Ca2+-, K+- and Na+-channels. To test the hypothesis that enhanced cardiac EET biosynthesis counteracts hypertrophy-induced electrical remodeling, male transgenic mice with cardiomyocyte-specific overexpression of the human epoxygenase CYP2J2 (CYP2J2-TG) and wildtype lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 40 publications
4
41
0
Order By: Relevance
“…The data show that the addition of BAPTA inhibited the ER stress response and stress-mediated apoptosis in Ang II-treated car- EET biosynthesis and heart disease development. CYP2J3 overexpression prevented the formation of arrhythmogenic substrates by maintaining gap junction integrity and reducing the development of atrial fibrosis in cardiac hypertrophy [16] . The upregulation of CYP2J3/11,12-EETs during ischemic post-conditioning (HPost) induced cardioprotection by inhibiting apoptosis via the mitochondrial pathway [18] .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The data show that the addition of BAPTA inhibited the ER stress response and stress-mediated apoptosis in Ang II-treated car- EET biosynthesis and heart disease development. CYP2J3 overexpression prevented the formation of arrhythmogenic substrates by maintaining gap junction integrity and reducing the development of atrial fibrosis in cardiac hypertrophy [16] . The upregulation of CYP2J3/11,12-EETs during ischemic post-conditioning (HPost) induced cardioprotection by inhibiting apoptosis via the mitochondrial pathway [18] .…”
Section: Resultsmentioning
confidence: 97%
“…Accumulating evidence suggests that EETs have crucial and diverse protective roles within the cardiovascular system. Specifically, EETs have been reported to possess antiarrhythmic [16] , anti-inflammatory [17] , anti-apoptotic [18] , and antioxidant [19] functions. Additionally, CYP2J3 overexpression and increased levels of EETs have been reported to decrease ER stress signaling and ER stress-mediated apoptosis in rats with heart failure by maintaining SERCA2a activity and intracellular Ca 2+ homeostasis [20] .…”
Section: +mentioning
confidence: 99%
“…Moreover, the circulating epoxy-metabolites that are predominantly esterifi ed with lipoprotein lipids may themselves become biologically active in other tissues after being released by lipoprotein lipases ( 81 ). There is increasing evidence for a cardioprotective role of CYP-epoxygenase metabolites from studies in animal models of ischemia/reperfusion injury, maladaptive cardiac hypertrophy, and arrhythmia ( 12,24,82 ). We showed that 17,18-EEQ and 19,20-EDP are potential candidates for mediating the antiarrhythmic effect of n-3 PUFAs ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, inhibition of sEH increases endogenous EETs, improves pressure overload heart failure and reduces the incidence of arrhythmias (67). Similarly, cardiac overexpression of CYP2J2 reduces mortality and arrhythmias in transverse aortic constriction and isoproterenol infusion models of heart failure compared to wild type mice (68). Angiotensin-induced cardiac fibrosis, inflammation and hypertrophy are also reduced in CYP2J2 mice (69, 70).…”
Section: Summary Of Cardiovascular Actions Of the Eetsmentioning
confidence: 99%